Traction suture modification to tongue-in-groove caudal septoplasty. Issue 2 (February 2018) - Indeyeva, Y.A.; Lee, T.S.; Gordin, E.; Chan, D.; Ducic, Y.
Abstract: Caudal septal deviation leads to unfavorable esthetic as well as functional effects on the nasal airway. A modification to the tongue-in-groove (TIG) technique to correct these caudal septal deformities is described. With placement of a temporary suspension suture to the caudal septum, manual traction is applied, assuring that the caudal septum remains in the midline position while it is being secured with multiple through-and-through, trans-columellar and trans-septal sutures. From 2003 to 2016, 148 patients underwent endonasal septoplasty using this modified technique, with excellent functional and cosmetic outcomes and a revision rate of 1.4%. This modified TIG technique replaces the periosteal suture that secures the caudal septum to the midline nasal crest in the original TIG technique. This simplifies the procedure and minimizes the risk of securing the caudal septum off-midline when used in endonasal septoplasty.